„Siła słabych więzi”, czyli (jeszcze raz) o maskującym języku socjologii - Drozdowski , Rafał (Człowiek i Społeczeństwo, 2012)
The article concerns on the Mark Granovetter’s concept of the strength of weak ties. The main question is about how it is used in theoretical and ideological disputes of latemodern society today. For some, a society based on weak ties is equivalent of increasing autonomy and individuality, but this is also the relaxation of the most repressive forms of social control. For others, weak social relationships are the evidence of a deep crisis of contemporary societies. The problem is that both, the first and the others speakers are using the term “strength of weak ties” mask the true picture of social reality. The first are blind on the process of society disintegration. Others – ignore the growing importance of social networks and do not appreciate the causal force of “minimal engagement”. The new technologies are able to aggregate these “minimal engagements” into a new powerful instrument of political, social and cultural impact.